Strengthening RC eccentrically loaded columns by CFRP at different levels of initial load. (1st April 2023) - Blikharskyy, Yaroslav; Selejdak, Jacek; Vashkevych, Rostyslav; Kopiika, Nadiia; Blikharskyy, Zinoviy
Highlights: The CFRP starts to work with the main reinforcement immediately after application. The previous loading has the influence on the efficiency of strengthening with CFRP. Lower values of preloading increase the strengthening effect. Abstract: This paper presents results obtained from test carried out to investigate the behavior of columns strengthened with CFRP laminates subjected to eccentrically applied axial loading. It is noted that when strengthening existing structures, it is often not possible to fully unload them and as a result the structural elements being strengthened are pre-loaded. In this research 10 large scale column specimens, strengthened with CFRP are investigated. Attention is focused on investigating the effect of pre-loading acting at the moment of strengthening on the recorded behavior. Each sample is initially loaded with eccentrically applied axial force, equal to 30%, 50% and 70% of the ultimate capacity. Once strengthened, the specimens were incrementally loaded until the destruction, values of strains and deflections were recorded on each loading stage. Strength, deformability and ductility parameters of columns were determined and thoroughly analyzed. Comparative analysis was carried out and the effectiveness of the strengthening is determined. It was identified, that the higher levels of initial loading decrease the strengthening effect from 31.8% to 15 % when for 30% and 70% preloading, respectively. Also, for samples with high pre-loading level the ultimate displacement at ultimate load reduced. It is important to note the increase of stiffness and decrease of deflections due to CFRP-strengthening. The presence on initial loading slightly decreases the ductility of CFRP strengthened columns (by 9–12 %). Specific features of CFRP effectiveness should be taken into account in engineering practice.